2017
DOI: 10.1515/cmam-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Super-Exponentially Convergent Parallel Algorithm for a Fractional Eigenvalue Problem of Jacobi-Type

Abstract: A new algorithm for eigenvalue problems for the fractional Jacobi type ODE is proposed. The algorithm is based on piecewise approximation of the coefficients of the differential equation with subsequent recursive procedure adapted from some homotopy considerations. As a result, the eigenvalue problem (which is in fact nonlinear) is replaced by a sequence of linear boundary value problems (besides the first one) with a singular linear operator called the exact functional discrete scheme (EFDS). A finite subsequ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The sufficient conditions of an exponential convergence rate and the absolute errors estimates of the proposed approach are received in Section 5. The obtained absolute errors estimates of the FD-method significantly improve the accuracy of the estimates obtained earlier in [5]. Derivation of the basic formulas for the proposed new symbolic algorithmic implementation of our method is given in Section 6 and in Appendices A, B, C. The numerical algorithm is given in Section 7.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…The sufficient conditions of an exponential convergence rate and the absolute errors estimates of the proposed approach are received in Section 5. The obtained absolute errors estimates of the FD-method significantly improve the accuracy of the estimates obtained earlier in [5]. Derivation of the basic formulas for the proposed new symbolic algorithmic implementation of our method is given in Section 6 and in Appendices A, B, C. The numerical algorithm is given in Section 7.…”
Section: Introductionmentioning
confidence: 69%
“…In [5] it was shown that the fourth order ordinary differential equation with all derivatives of the eigenfunction could be reduced to the form (1) using the variable transformation. That is why we consider the eigenvalue problem with equation (1).…”
Section: Problem Statementmentioning
confidence: 99%
See 3 more Smart Citations